Self-employed workers: industrial relations and working conditions (Dublin, 2009)
"This report presents an overview of the industrial relations and employment and working conditions of self-employed workers in the European Union and Norway. It presents basic trends in self-employment, highlights issues concerning the definition of self-employment and offers an overview of the national situations regarding the legal framework. The study also examines social security as a crucial aspect of the regulation of self-employment and a source of differences between employees and self-employed workers. Recent reforms in this area have often focused on increasing protection measures. Finally, the report analyses the presence and regulation of ‘economically dependent work’, as well as the collective representation of self-employed workers."